2020
DOI: 10.1002/fsn3.1377
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of conventional steam cooking and microwave cooking on cooked pigmented rice texture and their phenolic antioxidant

Abstract: The impact of two different cooking processes (microwave and steaming) on cooked rice quality (i.e., texture), and changes in the bioactive compounds (total phenolic content [TPC] and total anthocyanin content [TAC]) and antioxidant activities (DPPH and FRAP assays) of black and red (nonwaxy) and purple (waxy) pigmented rice were investigated. No significant difference in the firmness between microwave‐cooked rice and steam‐cooked rice was found, except for cooked purple rice. However, microwave cooking promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 49 publications
3
16
0
Order By: Relevance
“…Using an electric rice cooker retained anthocyanins in glutinous rice better than using the pressure-cooker method [ 62 ]. Microwave cooking conserved two- to three-fold higher anthocyanin content in glutinous and non-glutinous rice in comparison to steam cooking [ 119 ]. For Italian purple rice, no anthocyanin reduction was obtained after cooking using either a rice cooker or a water bath [ 120 ].…”
Section: Stability Of Grain Anthocyanin In Purple Rice During Post-harvest Processingmentioning
confidence: 99%
“…Using an electric rice cooker retained anthocyanins in glutinous rice better than using the pressure-cooker method [ 62 ]. Microwave cooking conserved two- to three-fold higher anthocyanin content in glutinous and non-glutinous rice in comparison to steam cooking [ 119 ]. For Italian purple rice, no anthocyanin reduction was obtained after cooking using either a rice cooker or a water bath [ 120 ].…”
Section: Stability Of Grain Anthocyanin In Purple Rice During Post-harvest Processingmentioning
confidence: 99%
“…Anthocyanins are water‐soluble pigments that belong to a subclass of flavonoids, which are located mainly in the pericarp of many varieties of pigmented grains, fruits, and vegetables (Thuengtung & Ogawa, 2020). Anthocyanins are easily degraded when they are exposed to heat, and the intensity of the thermal treatment determines the rate of oxidative degradation (Surh & Koh, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The results suggested that steaming preserved greater antioxidant content as compared to cooking in all treatments by all assays. The reductions in antioxidant activity values of rice after steaming and cooking treatment were the result of both thermal degradation of antioxidant compounds and possible leaching of water‐soluble compounds (Garretson et al, 2018; Harakotr et al, 2014; Kim et al, 2019; Thuengtung & Ogawa, 2020). The factors, including rice cultivar, severity of thermal treatment, and type of feedstock for cooking, can affect the antioxidant activity of free phenolic compounds in rice (Min et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the above, this behavior could be explained by the presence of water in which hydro-soluble phenolic compounds migrate during cooking. The migration of phenolics can also occur when rice is soaked in water prior to cooking [36]. Interestingly, when the rice was prepared by the cooker method, the water was still present at the end of the procedure and it showed considerable amounts of bioactive compounds for both the two pigmented rice cultivars investigated (Table 3), making the rice cooker the cooking method more suitable than water bath.…”
Section: Samplementioning
confidence: 99%